INNOVATIVE FACTORS AS THE DRIVING FORCE BEHIND THE DEVELOPMENT OF THE COMPETITIVENESS OF REGIONS OF THE SIBERIAN FEDERAL DISTRICT - S. Yakovlev (Вестник университета)
The dependence of the gross regional product per capita of some of the factors influencing the innovative development of the region: internal costs of research and development, the current internal development costs, the number of patents granted. For calculations using regression analysis of 12 regions of the Federal District of Russia on the basis of statistical data for the period from 2008 to 2012. The high dependence of the gross regional product per capita is one of the innovative factors.